Icebreakers for Adults - Megan Stein; Taylor Nash (EDIS)
Building rapport is key when creating a team culture. As groups change over time, it is imperative to continually reintroduce and reacclimate new team members to long-standing teammates. Leaders of groups that undergo constant change, like those whose jobs involve volunteers, may find it challenging to find innovative ways to bring people together. Icebreakers are quick, low- or no-cost activities that allow individuals to get to know the people around them and serve as a means to build trust and openness in a low-stakes environment. This new 3-page publication of the UF/IFAS Department of Agricultural Education and Communication outlines strategies to use when building a team culture and gives examples of simple activities to build cultures within teams or groups. Written by Megan Stein and Taylor Nash.